AI and IOT Based Algorithm for Cattle Lumpy Disease Detection - G E, Raghavendra Patil; Pati, Abinash; Raj, Ayush; Patidar, Navin; B H, Baba Fakruddin Ali; Priya, Siddhi (2025 International Conference on Computational Robotics, Testing and Engineering Evaluation (ICCRTEE), 2025)
Lumpy Skin Disease (LSD) is an infection brought on by Capri poxvirus, predominantly affecting cattle in Africa and the Middle East, with an increasing risk of spreading to Asia and Europe. This disease poses significant threats to international trade and has potential as a bioterrorism agent. Several factors like unavailability of vaccines, economic impacts brought about by COVID-19, sanctions, animal trade, and climate changes have contributed to its spread. This review encompasses LSD's pathology, transmission, epidemiology, diagnosis, and control measures. In response to these challenges, the study focuses on the development of a comprehensive system for early detection and monitoring of LSD in cattle. Utilizing Arduino technology and sensors, a health monitoring device has been designed to track critical parameters such as temperature, heart rate, and movement patterns. Complemented by Convolutional Neural Networks (CNNs) for image analysis, this system enables early detection of LSD through real-time data collection and analysis. The device ensures continuous monitoring and instant alerts, facilitating timely interventions and improved livestock management, particularly in remote areas with limited veterinary services. This new approach seeks to make livestock management more efficient and sustainable and, in the process, minimize the economic and health effects of LSD while helping to develop a more resilient agriculture sector.